2003
DOI: 10.1074/jbc.m302993200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mechanical Strain on the Function of Gap Junctions in Osteocytes Are Mediated through the Prostaglandin EP2 Receptor

Abstract: Fluid flow conditioned medium and PGE 2 stimulated cAMP production and PKA activity suggesting that PGE 2 released by mechanically stimulated cells is responsible for the activation of cAMP and PKA. The adenylate cyclase activators, forskolin and 8-bromo-cAMP, enhanced intercellular connectivity, the number of functional gap junctions, and Cx43 protein expression, whereas the PKA inhibitor, H89, inhibited the stimulatory effect of PGE 2 on gap junctions. These studies suggest that the EP 2 receptor mediates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
146
1
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(161 citation statements)
references
References 66 publications
6
146
1
8
Order By: Relevance
“…Many different signaling modules can activate PKA, including prostaglandins (e.g., PGE 2 ) through the prostanoid receptor ; inflammatory cytokines through interferon signaling (Liu et al, 2004), calcium flux, purinergic ( Jing et al; accompanying paper); and -adrenergic signaling. Because of recent evidence suggesting that PGE 2 is synthesized in response to shear stress (Cherian et al, 2003;Ogawa et al, 2014), and the proposed role of PGE 2 in embryonic hematopoiesis ), PGE 2 is a candidate upstream of PKA for the exploration of shear stress-mediated signaling (Diaz et al; accompanying paper). Indeed, PGE 2 can up-regulate BMP4 in human CD34 + cord blood cells (Goessling et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many different signaling modules can activate PKA, including prostaglandins (e.g., PGE 2 ) through the prostanoid receptor ; inflammatory cytokines through interferon signaling (Liu et al, 2004), calcium flux, purinergic ( Jing et al; accompanying paper); and -adrenergic signaling. Because of recent evidence suggesting that PGE 2 is synthesized in response to shear stress (Cherian et al, 2003;Ogawa et al, 2014), and the proposed role of PGE 2 in embryonic hematopoiesis ), PGE 2 is a candidate upstream of PKA for the exploration of shear stress-mediated signaling (Diaz et al; accompanying paper). Indeed, PGE 2 can up-regulate BMP4 in human CD34 + cord blood cells (Goessling et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of protein kinase A (PKA) and its downstream target cAMP response element-binding protein (CREB) by exogenous shear stress has been observed in diverse cell types, including chondrocytes and osteocytes (Cherian et al, 2003;Ogawa et al, 2014). The classic mechanism of PKA activation involves the binding of a ligand to a G proteincoupled receptor and activation of adenylyl cyclase, which converts ATP into the second messenger cyclic AMP (cAMP).…”
Section: Genomic Binding and Interaction Of Creb In K562 Cellsmentioning
confidence: 99%
“…These data suggest that the signaling molecule being communicated by Cx43 in response to FGF2 is probably between 1.2 and 0.3 kDa in mass and likely anionic. The possibility of the diffusion of lipophilic molecules, such as DAG or arachidonic acid, through gap junctions as signal molecules must be carefully considered, as recent data has suggested that prostaglandins are released from osteoblasts via Cx43 hemichannel activity in response to fluid flow (Cherian et al, 2003(Cherian et al, , 2005. Another class of molecules that should not be ignored are the inositol polyphosphates, which extend beyond just IP3 and calcium signaling to a diverse set of cellular functions (York et al, 2001).…”
Section: Molenmentioning
confidence: 99%
“…These conditional Cx43 knockout mice, which use a 2.3-kb collagen I promoter-driven Cre-recombinase to excise a floxed Cx43 allele in cells of the osteoblast lineage, exhibit severe osteopenia as a result of defective osteoblast function. Further, the skeletons of these animals have been shown to be refractory to the anabolic effects of intermittent PTH administration, indicating a critical role of Cx43 in coordinating cell function in response to anabolic cues.Relatively little is known about the precise molecular role of gap junctions in sensing and responding to biological cues during bone formation, though in the past decade critical insights have been gained into the importance of gap junctions in processes such as response to growth factors and hormones (Schiller et al, 1992;Chiba et al, 1994;Van der Molen et al, 1996;Civitelli et al, 1998;Schiller et al, 2001), mechanical load (Jorgensen et al, 1997(Jorgensen et al, , 2000Ziambaras et al, 1998;Romanello and D'Andrea, 2001;Saunders et al, 2001Saunders et al, , 2003Cherian et al, 2003Cherian et al, , 2005Taylor et al, 2007), bisphosphonates (Plotkin et al, 2002(Plotkin et al, , 2005, and interaction with other cells (Villars et al, 2002). Importantly, less still is known regarding the biologically relevant second messengers that osteoblast and osteocyte gap junctions communicate among cells, and many molecular mechanisms have yet to be deduced.…”
mentioning
confidence: 99%
“…For instance, gap junction-deficient cells are dramatically less responsive to diverse extracellular signals including PTH, 47 and especially relevant to this review, fluid flow 48,49 and electric fields, 50 than are wild-type osteoblastic cells. Furthermore, cyclic stretch has been shown to increase connexin 43 expression and gap junctional intercellular communication in osteoblastic cells in vitro, 51 and several groups [52][53][54][55] have demonstrated that fluid flow increases gap junction expression and function in osteocytic MLO-Y4 cells. In vivo, Lozupone et al 56 demonstrated that mechanical loading of rat metatarsal bones increased the incidence of osteocytic gap junctions, and Su et al 57 demonstrated that expression of connexin 43 by osteocytes is increased in areas of bone exposed to tension relative to areas exposed to compression or to control bone.…”
Section: Putative Mechanosensorsmentioning
confidence: 98%